Cyberstalking : vitimologia da perseguição virtual implacável - Sousa, Talitha Jesus Carmo (2023)
The present work analyzes the cyberstalking phenomenon with an emphasis on the victimology of virtual stalking, which often happens relentlessly. Thus, we seek to answer the following question: Does network society, supported by cyberspace, favor violent phenomena to the detriment of potential victims? The research is relevant, among other reasons, for trying to understand how cyberspace interferes in the daily life of social actors, as well as the perpetration and victimization of this phenomenon that intertwines and transforms social relations. The objective is to show the context of cyberstalking cases and analyze the interference of cyberspace and the support of network society, to understand the violent phenomena against potential victims. The research initially describes the conceptual overview on network society, by Manuel Castells, and on violence, focusing on the definition of the microphysics of violence by José Vicente Tavares dos Santos. Then, it brings the concept of stalking and the corresponding literature on the term. The analysis continues with the study of the Anisha case, which illustrates a virtual persecution in a practical way. The approach was qualitative, with an initial exploratory phase, followed by a descriptive one, with data collection done on the internet and with a case study design. The case of Anisha, present in the documentary named Dark Net, was analyzed, and interpreted through bibliographical content. The technique used was content analysis. The results confirm the favoring of violent phenomena to the detriment of potential victims, who are increasingly vulnerable in the face of the exponential growth of technology and network society. Cyberstalking has become a practice widely used to propagate this and other macro and micro violence.